Induction chemotherapy increases efficacy and survival rate of patients with locally advanced esophageal squamous cell carcinoma - Huang, Yuting; Chang, Jing; Guo, Xiaolei; Zhang, Chao; Ji, Wenping; Zhou, Shusheng; Wang, Chao; Zhang, Xu (Frontiers in Oncology, 2022)
Objective: The efficacy of concurrent chemoradiotherapy (CRT) after induction chemotherapy (IC) in the treatment of esophageal squamous cell carcinoma (ESCC) remains unclear. The purpose of this study was to explore the efficacy of IC in patients with ESCC. Methods: 124 patients with ESCC receiving CRT were included. Patients were divided into IC+CRT group and CRT group. Short-term and long-term efficacy as well as survival time of the two groups were compared, influencing factors of IC efficacy were investigated, and overall survival (OS) and progression-free survival (PFS) between the two groups were compared in different subgroups. Results: There was no significant difference in the objective response rate (ORR) between the two groups. After IC, the ORR was higher in patients with single-drug concurrent chemotherapy weekly and patients with effective IC. In the long-term efficacy, advanced clinical stage patients had a shorter PFS compared to early stage patients, and chemoradiotherapy mode ameliorates patients’ PFS. OS and PFS of IC+CRT group were longer than that of CRT group in both tumor diameter <5cm and single-drug chemotherapy weekly subgroups. In addition, OS of IC+CRT group was longer than that of CRT group in pathological grade G1-2 subgroup. Conclusions: IC improve the efficacy and survival rate of patients with locally advanced ESCC, and the benefits are more advantageous in subgroups of effective IC, pathological grade G1-2, tumor diameter < 5cm, single-drug concurrent chemotherapy weekly.